ChemInform Abstract: Magnesium Catalysis for the Hydroboration of Carbodiimides. Issue 40 (16th September 2016) - Weetman, Catherine; Hill, Michael S.; Mahon, Mary F.
Abstract: The complex MAC is found to be an effective precatalyst for the title reaction under mild conditions.